Efeito da adição de fibras da palma do licuri (syagrus coronata) no comportamento físico e mecânico de compósitos de matriz cimentícia - Guimarães, Elvio Antonino (2013)
This research was motivated by the requirement of asbestos s replacement in building systems and the need to generate jobs and income in the country side of the state of Bahia, Brazil. The project aimed at using fibers from licuri leaves (syagrus coronata), an abundant palm in the region, to produce composites appropriate for the sustainable production of cement fibre reinforced products in small plants. The composites were produced in laboratory using Portland cement CP-II-F32, sand, water, licuri palm fiber contents of 1.0, 1.5 and 2.0% by weight of binder (two different fiber length) and metakaolin. The latter was chosen as an additional binder for its efficiency to reduce the alkalinity of cementitious matrixes therefore preventing the degradation of vegetable fibers. The characterization of the composite components was carried out by sieving and laser particle size analyses, thermal analysis, fluorescence and X-ray diffraction. The composites performance was evaluated by 3- point-bending tests, compressive strength, ultrasound module of elasticity, free and restrained shrinkage, water capillarity absorption and apparent specific gravity. It has been found that the addition of fibers increased the time to onset of cracking over 200.00% and a 25% reduction in cracks opening in the restrained shrinkage test. The capillary absorption reduced about 25% when compared to fiber-free composites. It was also observed with regard to flexural strength, compressive strength and specific gravity, that the addiction of fibers did not affect the composite performance presenting similar results for compounds with and without fibers. In general it can be stated that the reinforced composite fibers of palm licuri presents physical and mechanical characteristics which enable them to be used in the intended proposals of this research